Retinal topography in two species of flamingo (Phoenicopteriformes: Phoenicopteridae). Issue 17 (19th March 2020) - Lisney, Thomas J.; Potier, Simon; Isard, Pierre‐François; Mentek, Marielle; Mitkus, Mindaugas; Collin, Shaun P.
Abstract: In this study, we assessed eye morphology and retinal topography in two flamingo species, the Caribbean flamingo ( Phoenicopterus ruber ) and the Chilean flamingo ( P. chilensis ). Eye morphology is similar in both species and cornea size relative to eye size (C:A ratio) is intermediate between those previously reported for diurnal and nocturnal birds. Using stereology and retinal whole mounts, we estimate that the total number of Nissl‐stained neurons in the retinal ganglion cell (RGC) layer in the Caribbean and Chilean flamingo is 1.70 and 1.38 million, respectively. Both species have a well‐defined visual streak with a peak neuron density of between 13, 000 and 16, 000 cells mm −2 located in a small central area . Neurons in the high‐density regions are smaller and more homogeneous compared to those in medium‐ and low‐density regions. Peak anatomical spatial resolving power in both species is approximately 10–11 cycles/deg. En‐face images of the fundus in live Caribbean flamingos acquired using spectral domain optical coherence tomography (SD‐OCT) revealed a thin, dark band running nasotemporally just dorsal to the pecten, which aligned with the visual streak in the retinal topography maps. Cross‐sectional images (B‐scans) obtained with SD‐OCT showed that this dark band corresponds with an area of retinal thickening compared to adjacent areas. Neither the retinal whole mounts, nor the SD‐OCT imaging revealed any evidence of a central fovea in either species. Overall, we suggest that eye morphology and retinal topography in flamingos reflects their cathemeral activity pattern and the physical nature of the habitats in which they live. Abstract : We investigated eye morphology and retinal topography in Caribbean and Chilean flamingos. Both species have a well‐defined visual streak, with the peak retinal ganglion cell densities located in a small central area. The organization of the visual system in these birds reflects their cathemeral activity pattern and the physical nature of the habitats in which they live.